2019
DOI: 10.2340/16501977-2636
|View full text |Cite
|
Sign up to set email alerts
|

AbobotulinumtoxinA and rehabilitation vs rehabilitation alone in post-stroke spasticity: An cost-utility analysis

Abstract: Using a tool named cost-utility analysis, this study investigated whether rehabilitation combined with a given drug (abobotulinumtoxinA) for post-stroke spasticity is cost-effective (i.e. affordable) vs rehabilitation alone for both the Italian National Health Service and society. Over a period of 2 years, this study shows that each additional year weighted for health-related quality of life (quality-adjusted life year; QALY) gained via rehabilitation combined with abobotulinumtoxinA vs rehabilitation alone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…An important and widely debated issue concerns the cost-utility of BTX-A compared to the benefit gained, particularly in treating post-stroke spasticity. Investigations have demonstrated that aboBTX-A adjunct to rehabilitation produces a higher number of quality-adjusted life years compared to rehabilitation alone either in treating ULS [79] or post-stroke spasticity [80], and this therapeutic approach might be a cost-effective healthcare program for treating these patients [80]. In the present review, none of the studies included reported the cost-effectiveness of high BTX-A injection in treating spasticity, regardless of the aetiology.…”
Section: Discussionmentioning
confidence: 79%
“…An important and widely debated issue concerns the cost-utility of BTX-A compared to the benefit gained, particularly in treating post-stroke spasticity. Investigations have demonstrated that aboBTX-A adjunct to rehabilitation produces a higher number of quality-adjusted life years compared to rehabilitation alone either in treating ULS [79] or post-stroke spasticity [80], and this therapeutic approach might be a cost-effective healthcare program for treating these patients [80]. In the present review, none of the studies included reported the cost-effectiveness of high BTX-A injection in treating spasticity, regardless of the aetiology.…”
Section: Discussionmentioning
confidence: 79%
“…In terms of costs, analyses were made from the point of view of society, the health care system, or at the clinic level. A study in Italy comparing treatment with aboBoNT-A and rehabilitation vs. rehabilitation alone found an improvement of 0.47 QALY more in the aboBoNT-A group over a 2-year period [29]. However, another study carried out by Doan et al [27] only found an improvement of 0.107 over 5 years of treatment with usual care and onaBoNT-A.…”
Section: Resultsmentioning
confidence: 97%
“…The intervention reported cost savings of £27 per patient; nevertheless, these results were also not significant (95% CI 2455.13 to 401.34, P = .91). A total of 3 meditated therapy interventions [48][49][50] concluded that meditated therapy was more effective and cheaper than usual care with incremental costeffectiveness ratio (ICER) values ranging from £192 to £12 214 (costs converted to price year 2020 sterling prices).…”
Section: Resultsmentioning
confidence: 99%